Brain activity associated with Dual‐task performance of Ankle motor control during cognitive challenge. Issue 8 (2nd July 2019) - Peters, Sue; Eng, Janice J.; Liu‐Ambrose, Teresa; Borich, Michael R.; Dao, Elizabeth; Amanian, Ameen; Boyd, Lara A.
Abstract: Introduction: Skilled Ankle motor control is frequently required while performing secondary cognitively demanding tasks such as socializing and avoiding obstacles while walking, termed "Dual tasking." It is likely that Dual‐task performance increases demand on the brain, as both motor and cognitive systems require neural resources. The purpose of this study was to use functional MRI to understand which brain regions are involved in resolving Dual‐task interference created by requiring high levels of Ankle motor control during a cognitive task. Methods: Using functional MRI, brain activity was measured in sixteen young adults during performance of visually cued Ankle plantar flexion to a target (Ankle task), a cognitive task (Flanker task), and both tasks simultaneously (Dual task). Results: Dual‐task performance did not impact the Ankle task ( p = 0.78), but did affect behavior on the Flanker task. Response times for both the congruent and incongruent conditions during the Flanker task were significantly longer ( p < 0.001, p = 0.050, respectively), and accuracy for the congruent condition decreased during Dual tasking ( p < 0.001). Activity in 3 brain regions was associated with Dual‐task Flanker performance. Percent signal change from baseline in Brodmann area (BA) 5, BA6, and the left caudate correlated with performance on the Flanker task during the Dual‐task condition ( R 2 = 0.261, p = 0.04; R 2 = −0.258, p = 0.04; R 2 = 0.303, p = 0.03, respectively). Conclusions: Performance of Ankle motor control may be prioritized over a cognitive task during Dual‐task performance. Our work advances Dual‐task research by elucidating patterns of whole brain activity for Dual tasks that require Ankle motor control during a cognitive task. Abstract : The purpose of this study was to use fMRI to understand which regions are involved in resolving Dual‐task interference associated with high levels of Ankle motor control during the Flanker cognitive task—activity in 3 brain regions (Brodmann area (BA) 5, BA6, and the left caudate) correlated with performance on the Flanker task during the Dual‐task condition ( r = 0.511, p = 0.04; r = −0.508, p = 0.04; r = 0.550, p = 0.03, respectively)—Ankle motor control is prioritized over a cognitive task during Dual‐task performance which suggests a trade‐off between cognitive demands and mobility that may impact performance of cognitively challenging tasks.